Nested polymerase chain reaction (PCR) targeting 16S rDNA for bacterial identification in empyema. (May 2014) - Prasad, Rajniti; Kumari, Chhaya; Das, B. K.; Nath, Gopal
Abstract : Background: Empyema in children causes significant morbidity and mortality. However, identification of organisms is a major concern. Objective: To detect bacterial pathogens in pus specimens of children with empyema by 16S rDNA nested polymerase chain reaction (PCR) and correlate it with culture and sensitivity. Method: Sixty-six children admitted to the paediatric ward with a diagnosis of empyema were enrolled prospectively. Aspirated pus was subjected to cytochemical examination, culture and sensitivity, and nested PCR targeting 16S rDNA using a universal eubacterial primer. Results: Mean (SD) age was 5·8 (1·8) years (range 1–13). Analysis of aspirated pus demonstrated total leucocyte count >1000×10 6 /L, elevated protein (≧20 g/L) and decreased glucose (≤2·2 mmol/L) in 80·3%, 98·5% and 100%, respectively. Gram-positive cocci were detected in 29 (43·9%) and Gram-negative bacilli in two patients. Nested PCR for the presence of bacterial pathogens was positive in 50·0%, compared with 36·3% for culture. Conclusion: 16S rDNA PCR improves rates of detection of bacteria in pleural fluid, and can detect bacterial species in a single assay as well as identifying unusual and unexpected causal agents.